Static Hand Gesture Recognition Based on Convolutional Neural Networks. (10th October 2019) - Pinto, Raimundo F.; Borges, Carlos D. B.; Almeida, Antônio M. A.; Paula, Iális C.
Abstract : This paper proposes a gesture recognition method using convolutional neural networks. The procedure involves the application of morphological filters, contour generation, polygonal approximation, and segmentation during preprocessing, in which they contribute to a better feature extraction. Training and testing are performed with different convolutional neural networks, compared with architectures known in the literature and with other known methodologies. All calculated metrics and convergence graphs obtained during training are analyzed and discussed to validate the robustness of the proposed method.